Corrosion mechanism of spray refractory in COREX slag with varying basicity. Issue 18 (15th December 2019) - Pan, Dunxiang; Zhao, Huizhong; Zhang, Han; Zhao, Pengda; Li, Yichong; Zou, Qingfeng
Abstract: Bauxite-based spray refractories typically exhibit excellent mechanical strength and wear resistance, and have been widely used as lining materials in various industrial furnaces for many years. However, smelting reduction ironmaking in the COREX-produced slag carried out under a gas flowing at a high speed causes refractory corrosion at high temperature. Herein, Al2 O3 –SiO2 –CaO spray refractories were fabricated, and corrosion tests were conducted in an air atmosphere using the formulated COREX slag by varying the slag basicity from 0.5 to 1.0. The mechanism underlying the corrosion between the fabricated spray refractories and formulated COREX slag was investigated via X-ray diffraction, scanning electron microscopy (backscattered electron image and energy-dispersive X-ray spectroscopy), and thermodynamic simulations to establish a new corrosion model. The results showed that after sintering at 1300 °C, the prepared specimens contained corundum, mullite, and anorthite as the major crystalline phases. The reaction and penetration layers were observed from the surface to the interior of the specimens after corrosion. A high-melting-point phase, Mg(Al, Fe)2 O4 spinel layer, was generated at the slag–refractory interface, which effectively protected the specimens from further interaction with the molten slag, and afforded better corrosion resistance. The reaction layer corroded due to the phase conversion into the Ca2 Al2 SiO7 in the matrix. The thermodynamic simulation results of the interaction between the slag and refractory were consistent with those of the corrosion test. The total corrosion depth of the specimen was optimum when the slag basicity was 0.9. This study investigates the optimal performance environment of the spray refractory inside the COREX and provides an effective guide for designing the phase composition of related refractories.